(3GdOdGdI ai JQGK eTcd GdMOjK (B: s (3OQGSI JMdjdjI (B= Semantics of the literature of the prophet 's problematic traditions , An analytic study / s - (3GdSYjO eMeO GdSYjO GdeQSi GdZRGhis; (3NWQi YQGHi (B: s; (3YHOGdcQje LHd (B: s ((3GdbGgQI (B: s (3GdSYjO eMeO GdSYjO GdeQSi GdZRGhi (B: s, 2020)
(3SYJ gPg GdOQGSI Gdi ERGdI GdETcGd GdPi jMOK Mhd CMGOjK UMjMI(B: (3fJjLI dJYGQV XGgQi Hjf GdMOjK h GdbQBf(B: (3Ch Hjf GdMOjK h MOjK CNQ(B: (3Ch Hjf GdMOjK h GdYbd(B: (3h Pdc Yf WQjb eG JhVMg GdOdGdI GdJQcjHjI(B: (3h GdUQajI(B: (3h GdeYLejI ef NdGd JQGK eTcd GdMOjK(B. (3MjK JgOa gPg GdOQGSI Gdi(B: (3HjGf GdCSHGH GddZhjI (B{u(32013(B} (3h HNGUI GdOdGdjI efgG (B- (3GdJi hbaJ hQGA Jhge MUhd JYGQV(B: (3Ch bOM ai HYV GdCMGOjK GdfHhjI GdTQjaI(B. (3JMdjd gPg GdCSHGH ai VhA GdeYWjGJ GddZhjI GdeNJdaI(B: (3h GdGLJgGO dERGdI GdETcGd(B. (3fJGFL GdQSGdI(B: (3fLMJ GdCWQhMI ai ERGdI GdETcGd Yf GdCMGOjK GdfHhjI GdUMjMI fJjLI JYGQVgG XGgQjG ef NdGd GdefgL GdhUai GdJMdjdi GdPi dG jcJai HhUa GdXGgQI(B: (3h EfeG jTQY ai JMdjd cd YfUQ HHjGf CUdg(B: (3h QCi GdHGMKjf ajg h Jbhjeg(B: (3eY GdELJgGO h EgeGd GdeHQQGJ ZjQ GdefWbjI(B: (3h GdEcJaGA HGdLhGfH GdOdGdjI(B: (3aVdG Yf GcJTGaGJ YdejI JJYdb HJMbjb eDdaGJ ai JQGK eTcd GdMOjKs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe GddZI GdYQHjI h BOGHgGs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdOdGdIs; (3JQGKs; (3eTcds